Characterization of cell fusion in an experimental mouse model of endometriosis. Issue 2 (9th October 2018) - Tal, A; Tal, R; Shaikh, S; Gidicsin, S; Mamillapalli, R; Taylor, H S
Abstract: Cell fusion is involved in the development of some adult organs, is implicated in the pathogenesis of specific types of cancer, and is known to participate in repair/regeneration processes mediated by bone-marrow-derived cells (BMDCs). Endometriosis is a disease characterized by growth of functional endometrial tissue outside of the uterine cavity. Endometriosis shares some molecular properties with cancer and BMDCs home to endometriosis lesions in a mouse model. Our objective was to determine if cell fusion can occur in endometriosis and establish whether bone-marrow-derived cells participate in cell fusion events in lesions. We employed a Cre-Lox system to identify cell fusion events in a mouse model of endometriosis. Fused cells were detected in endometriotic lesions, albeit at a low frequency (∼1 in 400 cells), localized to the stromal compartment, and displayed restricted proliferation. Using 5-fluorouracil-based nongonadotoxic bone marrow transplantation model, we demonstrate that bone marrow cells represent a principal cell source for fusion events in lesions. Cell fusion progeny uniformly lacked expression of selected markers of hematopoietic, endothelial, and epithelial markers, though they expressed the mesenchymal/stromal markers Sca-1 and CD29. This study is the first to describe the phenomenon of cell fusion in endometriosis and points to a mesenchymal population derived from cell fusion events with limited proliferative activity, properties previously attributed to endometrial stem cells. Their putative role in the pathogenesis of the disease remains to be elucidated. Abstract : Cells of the endometriotic lesion fuse with cells of the host animal; bone-marrow-derived cells recruited to the endometriosis lesion contribute to this process.